The Effect of The Blended Learning Model on The Improvement of Student Learning Outcomes - Badrus Badrus; Zaenal Arifin (Nazhruna: Jurnal Pendidikan Islam, 2021)
The purpose of the study was to analyze the effect of the blended learning model towards learning outcomes of the comprehension concepts and economic problems solving of Private Islamic High School students in Nganjuk Regency. The study used an experimental method, with a quasi-nonequivalent control group design. The research was conducted at Private Islamic High School Al Manar Prambon Nganjuk. The samples were conducted based on students' characteristics and similarities in economic topics. The experimental class was assigned to XI Social 1 and the control class was XI Social 2. The analysis technique used was descriptive statistical technique and two-ways MANAVA. Descriptive statistics were seen from the mean, standard deviation, variance, and presentation. The results of the MANAVA test analysis when viewed from the centroid pillar's trace, Wilks' lambda, hotelling's trace, and Roy's lambda root in the experimental class had a significance value of 0.000. The value was transformed to the Fisher distribution or F test, then it is smaller than α ˂ 0.050. The study shows that the blended learning model has an effect on the learning outcomes of comprehension concepts and economic problems solving of Private Islamic High School students.